2022
DOI: 10.1155/2022/6233217
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Flavonoid C-Glycosides as Promising Antidiabetics Targeting Protein Tyrosine Phosphatase 1B

Abstract: Protein tyrosine phosphatase 1B (PTP1B), a negative regulator of the insulin signaling pathway, has gained attention as a validated druggable target in the management of type 2 diabetes mellitus (T2DM). The lack of clinically approved PTP1B inhibitors has continued to prompt research in plant-derived therapeutics possibly due to their relatively lesser toxicity profiles. Flavonoid C-glycosides are one of the plant-derived metabolites gaining increased relevance as antidiabetic agents, but their possible mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Additionally, it is a tool that studies the possible biological activity impact that may arise from complex instability and conformational alteration of the enzyme because of ligand binding [ 59 ]. Hence, it is germane to study the behaviour of the compounds at the binding pocket of the enzyme to understand the stability, compactness, and flexibility of the (ligand-enzyme) complex [ 60 ]. The RMSD quantifies the thermodynamic conformational stability of a protein-ligand complex during the MDS period; a lower RMSD indicates greater stability [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is a tool that studies the possible biological activity impact that may arise from complex instability and conformational alteration of the enzyme because of ligand binding [ 59 ]. Hence, it is germane to study the behaviour of the compounds at the binding pocket of the enzyme to understand the stability, compactness, and flexibility of the (ligand-enzyme) complex [ 60 ]. The RMSD quantifies the thermodynamic conformational stability of a protein-ligand complex during the MDS period; a lower RMSD indicates greater stability [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosine residues of IR and IRS are dephosphorylated by PTP1B, which is one of the most well-studied tyrosine phosphatases, acting as a crucial negative regulator of the insulin signaling pathways [122]. PTP1B modulation may be valuable as a prospective therapeutic target for the treatment of T2D, and new PTP1B-targeting inhibitors or medications have been developed [123][124][125][126][127][128]. Due to comparatively lower toxicity, plant-derived medicines have become more prominent.…”
Section: Targeting Ptp1b In Insulin Resistance Treatmentmentioning
confidence: 99%
“…Due to comparatively lower toxicity, plant-derived medicines have become more prominent. Rampadarath et al suggested flavonoid C glycosides, particularly orientin, as a possible therapeutic agent in the management of T2D [124]. Low-molecular-weight polymannuronic acid phosphate (LPMP), according to studies by Li et al, may be a promising candidate for an antidiabetic medication since it can reduce oxidative stress and improve insulin sensitivity [127].…”
Section: Targeting Ptp1b In Insulin Resistance Treatmentmentioning
confidence: 99%
“…22 Protein tyrosine phosphatase 1B (PTP1B) negatively regulates cell signalling transmitted from leptin and insulin receptors and has been developed as a new target to cure obesity and type 2 diabetes mellitus (T2DM). 23 In addition, 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR) is a crucial target enzyme for cholesterol synthesis and has been developed as a target for the treatment of hyperlipidemia. 24 On the other hand, some known T2DM and obesity clinical drugs, such as acarbose and orlistat, have been associated with numerous side effects such as myopathy, abdominal pain, skin rash, abdominal distension, oily stool, and hepatotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, pancreatic lipase plays an important role in diseases related to lipid metabolism, especially obesity 22 . Protein tyrosine phosphatase 1B (PTP1B) negatively regulates cell signalling transmitted from leptin and insulin receptors and has been developed as a new target to cure obesity and type 2 diabetes mellitus (T2DM) 23 . In addition, 3‐hydroxy‐3‐methylglutaryl‐coenzyme A reductase (HMGCR) is a crucial target enzyme for cholesterol synthesis and has been developed as a target for the treatment of hyperlipidemia 24 .…”
Section: Introductionmentioning
confidence: 99%